Planning and Strategies for Maharah al-Kalam Learning Arabic Language in Madrasah - Bambang Bambang; Ilham Tanjung; Dahlan Hatoguan Ritonga; Lilit Pardomuan Hasibuan; Abdul Hakim Pohan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study aims to describe the planning and strategies for maharah al-kalam learning in madrasahs. This objective aligns with the significant role of speaking skills in language, as language is the primary communication in all languages, including Arabic. The research was conducted using a literature review, which involved analyzing data from articles, books, and other scientific works as the primary sources of information. The data was then analyzed using a qualitative comparative approach, comparing various opinions in these sources and establishing the researcher's position among the existing viewpoints. Based on the analysis, it is evident that there is a lack of established planning for maharah al-kalam learning in madrasahs. Currently, no available plan can serve as a reference to facilitate the implementation of maharah al-kalam learning and enable students to acquire Arabic speaking skills. Based on experts' opinions, recommended strategies for maharah al-kalam learning include the jigsaw technique, small group presentations, and gallery/poster sessions. Techniques such as matching and identifying exercises, pattern drills, and dialogues can be employed. Various media, such as display boards, whiteboards, artificial wall clocks, tours, flow charts, flashcards, and reading machines, can be utilized. It is important to note that this research is limited to descriptive studies. Future researchers can further explore implementing some identified strategies to enhance maharah al-kalam learning.